An Efficient EAP-Based Pre-Authentication for Inter-WRAN Handover in TV White Space - Wang, Cong (2017)
The IEEE 802.22 standard regulates wireless regional area network (WRAN) operating at the very high frequency and ultrahigh frequency television white space (TVWS) bands. WRAN supports extensible authentication protocol (EAP)-based authentication schemes. However, due to its public key cryptography operations, a full EAP-based authentication scheme is time-consuming, which is unacceptable for the WRAN handover process. In this paper, an efficient EAP-based pre-authentication scheme for inter-WRAN handovers (EPW) in TVWS is proposed. By applying the proposed pre-authentication scheme, the customer premises equipment and the target secondary user base station can accomplish a seamless handover using symmetric key. Through logic derivation by Burrows, Abadi, and Needham logic and formal verification by automated validation of Internet security protocols and applications, we conclude that the proposed EPW scheme can obtain mutual authentication and maintain key secrecy with a high resistance to attack. Additionally, the performance of the EPW scheme has been investigated by simulation experiments. The results show that the EPW scheme provides a lower computation delay than that mandated by the security scheme regulation of the IEEE 802.22 standard.